Protein Chromatography Methods and Protocols - Walls, Dermot.; Walls, Dermot.; Loughran, Sinéad T.; Loughran, Sinéad T. (Methods in Molecular Biology, 2011)
A prerequisite for elucidating the structure and function of any protein is the prior purification of that protein. This necessity has led to the development of many purification schemes and chromatographic methods for the isolation of native proteins from complex sources. In Protein Chromatography: Methods and Protocols, leading researchers present clear protocol-style chapters that are suitable for newcomers and experts alike. The book opens with vital topics in protein biochemistry, addressing such areas as protein stability and storage, avoiding proteolysis during chromatography, protein quantitation methods including immuno-qPCR, and the contrasting challenges that microfluidics and scale-up production pose to the investigator, and then it segues into key methods involving the generation and purification of recombinant proteins through recombinant antibody production and the tagging of proteins, amongst other means, as well as many variations on classic techniques such as ion-exchange and immunoaffinity chromatography. Written in the highly successful Methods in Molecular Biology™ series format, protocols chapters include introductions to their respective subjects, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and up-to-date, Protein Chromatography: Methods and Protocols will greatly aid scientists in establishing these essential techniques in their own laboratories and furthering our understanding of the many imperative functions of proteins.